2017
DOI: 10.7717/peerj.3802
|View full text |Cite
|
Sign up to set email alerts
|

Light induced intraspecific variability in response to thermal stress in the hard coral Stylophora pistillata

Abstract: Recent research suggests that prior exposure of several months to elevated irradiance induces enhanced thermal tolerance in scleractinian corals. While this tolerance has been reported at the species level, individual coral colonies may react differently due to individual variability in thermal tolerance. As thermal anomalies are predicted to become common in the upcoming future, intraspecific variation may be key to the survival of coral populations. In order to study light-history based thermal stress respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Much work has been carried out on the individual effects of increased temperature, light, and feeding on coral physiology (e.g., [20,47,48]), but only one has tested the multistressor effects of all three simultaneously [49]. This study found feeding and low light levels to mitigate the negative effects of elevated temperature on chlorophyll a concentrations and photosynthetic rates in Turbinaria reniformis and Stylophora pistillata.…”
Section: Introductionmentioning
confidence: 98%
“…Much work has been carried out on the individual effects of increased temperature, light, and feeding on coral physiology (e.g., [20,47,48]), but only one has tested the multistressor effects of all three simultaneously [49]. This study found feeding and low light levels to mitigate the negative effects of elevated temperature on chlorophyll a concentrations and photosynthetic rates in Turbinaria reniformis and Stylophora pistillata.…”
Section: Introductionmentioning
confidence: 98%
“…Out of the four assessed methods, the glue method, which works well for hard corals (see e.g ., Tilstra et al, 2017 ), demonstrated the lowest success rate. Only 1 out of 20 fragmented colonies attached to the coral plug, albeit on the side of the plug.…”
Section: Discussionmentioning
confidence: 96%
“…Muir et al (2017) found species identity explained 33.2% of the variation in observed bleaching and identified species lineages of either high or low relative extinction risk. Tilstra et al (2017) demonstrated intra-individual variability in physiological responses of the scleratinian coral Stylophora pistillata, which may be attributed to differences amongst the spatially distinct clades for this coral species. Overall some genera are considered highly susceptible to bleaching stress, also shown among species variation (Muir et al, 2017).…”
Section: Artificial Shadingmentioning
confidence: 92%
“…Regardless of the shade source (natural or artificial), the reviewed literature demonstrates that different coral species may respond differently (i.e., interspecific, intraspecific and even intracolonial variations) to variable levels of light and stressors (Tilstra et al, 2017;Mizerek et al, 2018;Wangpraseurt et al, 2019;Kuanui et al, 2020;Dobson et al, 2021). Muir et al (2017) found species identity explained 33.2% of the variation in observed bleaching and identified species lineages of either high or low relative extinction risk.…”
Section: Artificial Shadingmentioning
confidence: 99%